Evaluation of Tumor Control Probability and Normal Tissue Complication Probability of Breast Cancer Treatment Plan in Post Mastectomy Radiation Therapy - Herwiningsih, S.; Yuana, F.; Latifah, R.; Hidayat, A.; Rahmahtullah, D. P.; Alviani, I.; Hentihu, F. K. (Atom Indonesia, 2024)
Radiotherapy has been widely used to treat cancer, including breast cancer treatment, which can be given after patients undergo mastectomy procedures. This study aims to evaluate tumor control probability (TCP) and normal tissue complication probability (NTCP) of three-dimensional conformal radiation therapy (3DCRT) and intensity modulated radiation therapy (IMRT) treatment planning in post-mastectomy breast cancer radiation therapy. Twenty clinical breast cancer treatment plans delivered using 3DCRT were evaluated retrospectively. The IMRT plans were created for the same patients. The dose-volume histograms of each plan were extracted from the Treatment Planning System (TPS) computer which were then used to compute the TCP and NTCP for each plan. The TCP was calculated using the Poisson model and the NTCP was calculated using the Lyman-Kutcher-Burman (LKB) model. The NTCP was calculated for normal lung tissue, heart, esophagus, and spinal cord. The results show that the TCP of the 3DCRT and IMRT plans are not significantly different, with a value of above 99 %. The NTCP of the left lung is lower in the IMRT plans while the NTCP of the esophagus is lower in the 3DCRT plans. The NTCP for the heart, spinal cord, and right normal lung are zero in all plans.